TINGKAT PENGETAHUAN IBU RUMAH TANGGA TENTANG PROGRAM IMUNISASI DI DESA SEMELINANG DARAT KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Elissa Jasmin; M. Razif " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Immunisation is a way to actively improve one's immunity against an antigen, so that if one day he is exposed to the same antigen does not cause disease. The purpose of this study was to determine what factors influence the level of knowledge housewife on immunization programs and to determine the extent of knowledge about the housewife in the village immunization program Semelinang Army. The theory used in this research is the theory of motivation. Motivation is the impulse that arises in a person is consciously or unconsciously to act with a certain purpose or can also be regarded as a business that can cause a person or group of people motivated to do something because they want mencxapai objectives to be achieved.Keywords: Immunization, level of knowledge, motivation